Participation of Jordanian Women in Elected Local Councils: Study in Municipal Elections and Decentralization - Tarawneh, Bashar (Dirasat: Human and Social Sciences, 2020)
This study aims at identifying the participation of Jordanian women in the elected local councils in Jordan (Municipality and Decentralization) during the study of municipal elections and decentralization in 2017 and the re-election held in 2018 in general Al-Muwaqqar area for elected local councils (municipal and decentralized) , And used the descriptive analytical method and the law. The study reached several results, the most important of which were: First, the election laws helped encourage the participation of Jordanian women and their representation in elected local councils as a result of the difficulties encountered in each electoral process. Second: The results of the elections that took place in 2017 highlighted the high participation and representation of women in the municipal elections and decentralization. As for the re-election held in 2018 in al-Muwaqqar area, the participation and representation of women in municipal elections increased. The study recommended the following: First, to continue applying the quota of women in all the elections taking place in Jordan, in particular the elections of the elected local councils (municipal and decentralization). Second, the Jordanian governments should raise the awareness of the Jordanian people, especially the remote areas, of the importance of representing Jordanian women in all the elections taking place in Jordan.